2005
DOI: 10.1038/nn1440
|View full text |Cite
|
Sign up to set email alerts
|

A positive autoregulatory loop of Jak-STAT signaling controls the onset of astrogliogenesis

Abstract: During development of the CNS, neurons and glia are generated in a sequential manner. The mechanism underlying the later onset of gliogenesis is poorly understood, although the cytokineinduced Jak-STAT pathway has been postulated to regulate astrogliogenesis. Here, we report that the overall activity of Jak-STAT signaling is dynamically regulated in mouse cortical germinal zone during development. As such, activated STAT1/3 and STAT-mediated transcription are negligible at early, neurogenic stages, when neurog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
346
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(370 citation statements)
references
References 50 publications
22
346
0
2
Order By: Relevance
“…The Jak/STAT pathway modulates astrogliosis and/or astrogliogenesis (Bonni et al, 1997;Sriram et al, 2004;He et al, 2005). It should be mentioned that ACM, but not METH itself, induced the differentiation of NSCs into GFAP-positive astrocytes via the Jak/STAT pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Jak/STAT pathway modulates astrogliosis and/or astrogliogenesis (Bonni et al, 1997;Sriram et al, 2004;He et al, 2005). It should be mentioned that ACM, but not METH itself, induced the differentiation of NSCs into GFAP-positive astrocytes via the Jak/STAT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Jak/STAT pathway has been postulated to regulate astrogliosis and astrogliogenesis (Bonni et al, 1997;Sriram et al, 2004;He et al, 2005). The place preference produced by MRP (3 mg/kg, s.c.), was significantly suppressed by intra-N.Acc.…”
Section: The Implication Of Jak/stat Pathway In the Enhancement By Acmentioning
confidence: 99%
“…Furthermore, the forced expression of the EGF receptor in early progenitors induces precocious astrocyte differentiation in response to LIF by increasing STAT3 protein levels (68), showing that, during the neurogenic period, the Jak/STAT pathway is only weakly activated. Recently, He et al (41) reported a positive autoregulatory loop of the Jak/STAT pathway, by which STAT1/3 directly activates the expression of many components of this pathway. This feed-forward loop provides a positive mechanism to direct the progenitor stem cells toward astrogliogenesis, showing that sufficient activation of the Jak/ FIGURE 14.…”
Section: Discussionmentioning
confidence: 99%
“…LIF may promote glial cell fate at the expense of the neuronal lineage in vivo, as it does in vitro (Bonni et al, 1997;Chang et al, 2004;Barnabe-Heider et al, 2005;He et al, 2005), which could explain the depletion of neuronal cells in the SVZ. Consistent with this hypothesis, phenotypic analysis in periventricular areas and the cortex of Ad:LIF-treated animals reveals a threefold to fivefold increase in BrdUϩ cells expressing Olig2 or S100, two glial cell markers (Fig.…”
Section: Lif Stimulates the Proliferation Of Parenchymal Glial Progenmentioning
confidence: 99%
“…LIF signaling activates the Jak (Janus kinase)/STAT (signal transducer and activator of transcription) and MAP (mitogen-activated protein) kinase pathways, which promote astrogliogenesis in vitro (Bonni et al, 1997;Molne et al, 2000;Viti et al, 2003;Chang et al, 2004;Barnabe-Heider et al, 2005;He et al, 2005). In addition, LIF is well known for promoting mouse embryonic stem (ES) cell selfrenewal (Williams et al, 1988) and the long-term growth of embryonic human NSCs in culture (Wright et al, 2003).…”
Section: Introductionmentioning
confidence: 99%